Central exclusive production of η and η0 mesons in diffractive proton-proton collisions at the LHC within the tensor-pomeron approach - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physical review, 2025)
We present a study of the central exclusive production (CEP) of 𝜂 and 𝜂′⁡(958) mesons in diffractive proton-proton collisions at high energies. The amplitudes, including pomeron and 𝑓2⁢ℝ reggeon exchanges, are calculated within the tensor-pomeron model. Absorption effects are also taken into account at the amplitude level. We fit some undetermined model parameters (coupling constants and cutoff parameters in form factors) to the WA102 experimental data and then make predictions for the LHC energy √𝑠=13 TeV. Both total cross sections and several differential distributions are presented. For 𝑝⁢𝑝 →𝑝⁢𝑝⁢𝜂, we find an upper limit for the total cross section of 2.5 μ⁢b for pseudorapidity of the 𝜂 meson |𝜂𝑀|<1 and 5.6 μ⁢b for 2<𝜂𝑀<5. For 𝑝⁢𝑝 →𝑝⁢𝑝⁢𝜂′, we predict the cross section to be in the range of 0.3-0.7 μ⁢b for pseudorapidity of the 𝜂′ meson |𝜂𝑀| <1 and 0.9-2.1 μ⁢b for 2 <𝜂𝑀 <5. This opens the possibility to study diffractive production of pseudoscalar mesons in experiments at the LHC. We discuss if there are arguments from SU(3)-flavor symmetry which would forbid pomeron-pomeron fusion giving an 𝜂 meson. In our opinion such arguments do not exist. We also consider CEP of the pseudoscalars 𝜂 and 𝜂′⁡(958) and the pseudovector meson 𝑓1⁡(1285) in diffractive proton-proton collisions in a theory with a scalar pomeron. We show that none of these particles can be produced in this way in the scalar-pomeron theory. Thus, experimental observation of any of these particles in the above CEP processes at the LHC would give striking evidence against a scalar character of the pomeron.